2008
DOI: 10.1071/ea07108
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of perennial pasture legumes and herbs to identify species with high herbage production and persistence in mixed farming zones in southern Australia

Abstract: Ninety-one perennial legumes and herbs (entries) from 47 species in 21 genera were evaluated at sites in New South Wales, South Australia and Western Australia over 3 years from 2002 to 2005 to identify plants with superior herbage production, persistence and the potential to reduce ground water recharge. Evaluation was undertaken in three nurseries (general, waterlogged soil and acid soil). Medicago sativa L. subsp. sativa (lucerne) cv. Sceptre was the best performing species across all sites. In the general … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
61
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(63 citation statements)
references
References 36 publications
0
61
1
Order By: Relevance
“…The results from the current study are complemented by those from later studies of mostly perennial legumes reported by Li et al (2008), Boschma et al (2010a) and Boschma et al (2011) for a site on a Brown Vertosol soil, near Manilla on the North-West Slopes of NSW, which included entries of sulla, Onobrychis viciafolia Scop. (sainfoin) and lucerne.…”
Section: Discussionmentioning
confidence: 56%
“…The results from the current study are complemented by those from later studies of mostly perennial legumes reported by Li et al (2008), Boschma et al (2010a) and Boschma et al (2011) for a site on a Brown Vertosol soil, near Manilla on the North-West Slopes of NSW, which included entries of sulla, Onobrychis viciafolia Scop. (sainfoin) and lucerne.…”
Section: Discussionmentioning
confidence: 56%
“…By harvesting a much larger portion of the seasonally available water, nutrients and photosynthetic energy, many perennials achieve higher net primary productivity in contrast to annuals in both natural and agro-ecosystems [24,76]. Therefore, promising perennial grain legume candidates will be highly productive during the entirety of the season and capable of producing large quantities of biomass while persisting in the cropping system for multiple years [77,78]. Sun-adapted legumes may be more productive than shade-adapted legumes in agricultural settings by becoming light saturated at higher levels of photosynthetic active radiation (having a greater radiation use efficiency), thus having higher maximal carbon assimilation rates [79].…”
Section: Yield Potentialmentioning
confidence: 99%
“…Many perennial species, by virtue of their large active root systems and specialized root structures (tubers or crowns), are able to efficiently capture, respond to and/or store available water [15,109]. Some potential alternative legumes are already being evaluated specifically for that ability [78,83]. Additionally, other legumes have strategies for acquiring phosphorous (the second most limiting element to plant growth behind N) via specialized root structures (e.g., cluster roots), by releasing carboxylates into surrounding soils and through arbuscular mycorrhizal associations [110,111].…”
Section: Resource Acquisition and Retentionmentioning
confidence: 99%
“…Due to its commercial value and high management requirements, coupled with the restriction of seed importation, lucerne also experienced a sustained breeding effort in Australia Clements 1989;Irwin et al 2001). Recently, when 91 perennial legumes and herbs representing 47 species in 21 genera were evaluated over 3 years for herbage production, persistence and the potential to reduce ground water recharge at sites in New South Wales, South Australia and Western Australia, lucerne was reported to be the best performing species across all sites (Li et al 2008). Therefore, lucerne's role as the best performing forage legume in Australian pastoral agriculture has been, and continues to be, high.…”
Section: Introductionmentioning
confidence: 99%